Бастапқы әскери дайындықтағы ақпараттық жүйелер - Боранкулова, Г.С.; Төреханова, Г.И. (My University, 2013)
This article examines the role and place of information technologies in all spheres of life, including the improvement of military training, the development of scientific and technological progress and the realization of its significance and necessity.